Effect of inoculants on the fermentation of wheat, alfalfa, and sorghum silages - K. Bolsen; R. Smith; H. Ilg; Daniel Y.C. Fung (Kansas Agricultural Experiment Station Research Reports, 1986)
Results from three laboratory silo experiments showed that four commercial silage inoculants increased fermentation rate, particularly during the first 4 days of the ensiling process. The effects of the additives on pH drop and lactic acid production were greater in wheat and alfalfa than in forage sorghum.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Fermentation; Wheat; Alfalfa; Sorghum silage